Pelatihan Bnatuan Hidup Dasar Bagi Masyarakat Awam Di Klaurahan Buntalan, Kecamatan Klateng Tengah, Klaten - Saifudin Zukhri; Cahyo Pramono (Universitas Muhammadiyah Klaten, 2024)
Emergency conditions that result in cardiac arrest and heart rhythm can lead to rapid death. A delay of 4 minutes will cause the brain not to get enough blood supply and brain damage, and if there is a delay of 10 minutes, it can cause tissue death in the brain. Appropriate preparedness in the form of training for the general public in providing basic life support is expected to be faster and more relevant so that it can minimize deaths due to cardiac arrest in the community. This community service aims to increase the ability of the general public to provide basic life support (BHD) to cardiac arrest patients in the community. The BHD training for the general public was held on June 13, 2024, from 14.00-16.00 WIB, attended by 14 participants at the University of Muhammadiyah Klaten Campus. The methods used are lectures, questions and answers, and demonstrations. The material provided was cardiopulmonary resuscitation for lay helpers (Hand only CPR). The results of the pretest showed that the average score of the participants, for the score range of 0-10 was 4.57, while the average score of the posttest was 9.07. The paired t-test results showed a significant difference in score between before and after training (p=0.001). The results of the assessment of the participant's ability to carry out basic life support were 13 participants in the good category (score ≥75), and 1 participant in the fairly good category (score 70-74), with an average score of 77.4 (score range 1-100). Lay BHD training with lecture and demonstration methods can improve the community's ability to provide basic life support to cardiac arrest patients. Similar training needs to be implemented widely so that the number of ordinary people who are able to provide basic life assistance is larger. Keywords: cardiac arrest, basic life support, lay person.